Optimization of capacitated vehicle routing problem with alternative delivery, pick-up and time windows: A modified hybrid approach - Sitek, Paweł; Wikarek, Jarosław; Rutczyńska-Wdowiak, Katarzyna; Bocewicz, Grzegorz; Banaszak, Zbigniew (Neurocomputing (Amsterdam), 2021)
In this paper, the optimization of Capacitated Vehicle Routing Problem with Alternative Delivery, Pick-up and Time windows is considered. The development of this problem was motivated by analysis of postal and courier delivery issues. In some generalization, the problem examined can be classified as a combination of many variants of the classical VRP (Vehicle Routing Problem), such as CVRP (Capacitated Vehicle Routing Problem), VRPPD (Vehicle Routing Problem with Pickup and Delivery), VRPTW (Vehicle Routing Problem with Time Windows), etc. What distinguishes the presented problem from known variants of VRPs is the introduction of alternative delivery points and parcel lockers incorporated into the distribution network and the ability to take into account logical constraints. The problem model was formulated in the form of BIP (Binary Integer Programming). Moreover, the original hybrid approach integrating CP (Constraint Programming), GA (Genetic Algorithm) and MP (Mathematical Programming) was proposed for the model implementation and optimization. Numerous computational experiments verifying the correctness of the model and the effectiveness of the hybrid approach were also presented.